C5 and C6 human dermatomes: A clinical, electromyographical, imaging and surgical findings - De Souza Faleiros, Antonio Tadeu [UNESP]; De Lima Resende, Luiz Antonio [UNESP]; Zanini, Marco Antonio [UNESP]; De Lima Castro, Heloisa Amélia; Gabarra, Roberto Colichio [UNESP] (FapUNIFESP (SciELO), 2009)
There is substantial controversy in literature about human dermatomes. In this work, C5 and C6 superior limb dermatomes were studied. The method consisted of comparing clinical signs and symptoms with conduction studies, electromyographical data, neurosurgical findings, and imaging findings obtained by computerized tomography (CT) or magnetic resonance imaging (MRI), for each patient. Data analysis from superior members in 18 patients suggests that C5 is located in the lateral aspect of the shoulder and arm, and C6 in the lateral aspect of the forearm and 1st, 2nd, and 3rd fingers. To our knowledge this is the first time that C5 and C6 human dermatomes have been studied by all the following methods together: clinical, electromyographical, CT and MR imaging, and surgical findings.
Keywords: Eletromyography; Human dermatome; Imaging; Superior member